Changing practice: red blood cell typing by molecular methods for patients with sickle cell disease. Issue 6 (9th January 2015) - Casas, Jessica; Friedman, David F.; Jackson, Tannoa; Vege, Sunitha; Westhoff, Connie M.; Chou, Stella T.
Abstract : Background: Extended red blood cell (RBC) antigen matching is recommended to limit alloimmunization in patients with sickle cell disease (SCD). DNA‐based testing to predict blood group phenotypes has enhanced availability of antigen‐negative donor units and improved typing of transfused patients, but replacement of routine serologic typing for non‐ABO antigens with molecular typing for patients has not been reported. Study Designs and Methods: This study compared the historical RBC antigen phenotypes obtained by hemagglutination methods with genotype predictions in 494 patients with SCD. For discrepant results, repeat serologic testing was performed and/or investigated by gene sequencing for silent or variant alleles. Results: Seventy‐one typing discrepancies were identified among 6360 antigen comparisons (1.1%). New specimens for repeat serologic testing were obtained for 66 discrepancies and retyping agreed with the genotype in 64 cases. One repeat Jk(b−) serologic phenotype, predicted Jk(b+) by genotype, was found by direct sequencing of JK to be a silenced allele, and one N typing discrepancy remains under investigation. Fifteen false‐negative serologic results were associated with alleles encoding weak antigens or single‐dose Fy b expression. Conclusions: DNA‐based RBC typing provided improved accuracy and expanded information on RBC antigens compared to hemagglutination methods, leading to its implementation as the primary method for extended RBC typing for patients with SCD at our institution.